A formação inicial de professores e a educação inclusiva: analisando as propostas de formação dos cursos de licenciatura da UFPA - MESQUITA, Amélia Maria Araújo (Universidade Federal do Pará, 2011)
The objective of this study is to analyze new proposals in the formal preparation of teachers, developed by the education licensure programs at UFPA, Guamá campus. These proposals were created in the context of adherence to the educational policies of inclusion and their subsequent legislation, adopted by the Brazilian government. To accomplish this objective, I sought in official documents (looking specifically for theoretical references to inclusion and the formation of teachers) indicators that presented themselves as means to analyze the political educational projects in licensure programs which have been reformulated after, or contemporaneously with, the creation of the DCN for the formation of basic education teachers. The goal was also to discover indicators which could perceive whether or not these licensure programs adhered to the official prescriptions and orientation for dealing with question of diversity. 1) Achieving the requisite amount of topics in formal preparation; 2) the re-defining of pedagogic disciplines and; 3) the inclusion of content or disciplines related to the education of people with special educational needs in the curriculum of licensure programs were the indicators found within the educational policies that could be used as indices in the new proposals for preparing basic education teachers in the licensure programs at UFPA to work in inclusive schools. In the analysis of the projects, I identified that the seven programs studiedGeography, History, Letters, Chemistry, Biology, Math, and Physical Educationmet the first two prescriptions. However, in respect to the inclusion of people with special educational needs (NEE), the paths taken were different. Geography and Physical Education included teaching methods; Letters, Biology and History included some topics; while Math and Chemistry did not meet this requirement. Using these data I sought, using a semi-structured interview, to analyze the arguments made by the programs to justify their decisions. These interviews were conducted only with the Letters, Chemistry, and Physical Education programs. The interviews allowed me to discover that inclusion was not the impetus that oriented the curricular reformation process and, that despite finding methods and topics present in the majority of education programs, they have not redirected the formation process of teachers. The absent presence of inclusion in a large part of education programs at UFPA, demonstrates that the official policy at the university seems to be merely an attempt to meet the basic official requirements set by the Brazilian legislature.